2012
DOI: 10.1590/s0100-69912012000400003
|View full text |Cite
|
Sign up to set email alerts
|

Experiencia en dos hospitales de tercer nivel de atención del suroccidente de Colombia en la aplicación del Registro Internacional de Trauma de la Sociedad Panamericana de Trauma

Abstract: It was determined the needing for the TRS implementation and the mechanisms to provide continuity. The registry becomes an information source for the investigation developing. It was identified the causes of consult, morbidity and death due to trauma that will allow a better planning of the emergency services and of the regional trauma system in order to optimize and reduce the attention costs. Based on optimal information system it will be able to present the necessary adjusts to redesign the Trauma and Emerg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
13

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 7 publications
1
10
0
13
Order By: Relevance
“…Although the statistics, which for years have revealed the state of insecurity in Cali, and the evident need of implementing a trauma registry, the first pilot program of the first trauma registry in the city (International Trauma System Development Program-ITSD) did not begun until 2011 16 . This program allowed the identification of the reasons for the consultation, mechanism of trauma, trauma index, mortality, and other variables.…”
Section: Discussionmentioning
confidence: 99%
“…Although the statistics, which for years have revealed the state of insecurity in Cali, and the evident need of implementing a trauma registry, the first pilot program of the first trauma registry in the city (International Trauma System Development Program-ITSD) did not begun until 2011 16 . This program allowed the identification of the reasons for the consultation, mechanism of trauma, trauma index, mortality, and other variables.…”
Section: Discussionmentioning
confidence: 99%
“…In a scoping review of world trauma registries in 2012, publications from trauma registries were identified from 35 countries with the majority of publications from the US and Australia [ 27 ]. Trauma registries can be used as part of a trauma quality improvement programme [ 9 , 29 ]. Implementation of trauma quality improvement programmes, which include trauma registries, has resulted in decreased mortality from trauma [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…A trauma registry may be defined as “a timely, accurate, and comprehensive data source that allows for continuous monitoring of the process of injury care” [ 26 ]. The data encompasses all hospital trauma-related admissions and is a powerful tool for identifying injury trends and possible solutions [ 4 , 29 ]. Trauma registry data are particularly valuable in LMICs because other sources of data, which might be available in high-income countries, are less accessible in LMICs [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…In our circle, there is a subregistry of trauma mechanisms and its secondary complications. However, in a study conducted in 2 hospitals of 2nd and 3rd level of a Colombian city (Cali-Valle del Cauca) it was determined that the stab wound represents the 10.6% as a mechanism of injury and represents the 5th cause of death by trauma constituting 4.1% [10].…”
Section: Discussionmentioning
confidence: 99%